Tools for the diagnosis of hepatitis C virus infection and hepatic fibrosis staging - Saludes, Verónica (Baishideng Publishing Group Co., Limited, 2014)
Hepatitis C virus (HCV) infection represents a major public health issue. Hepatitis C can be cured by therapy, but many infected individuals are unaware of their status. Effective HCV screening, fast diagnosis and characterization, and hepatic fibrosis staging are highly relevant for controlling transmission, treating infected patients and, consequently, avoiding end-stage liver disease. Exposure to HCV can be determined with high sensitivity and specificity with currently available third generation serology assays. Additionally, the use of point-of-care tests can increase HCV screening opportunities. However, active HCV infection must be confirmed by direct diagnosis methods. Additionally, HCV genotyping is required prior to starting any treatment. Increasingly, high-volume clinical laboratories use different types of automated platforms, which have simplified sample processing, reduced hands-on-time, minimized contamination risks and human error and ensured full traceability of results. Significant advances have also been made in the field of fibrosis stage assessment with the development of non-invasive methods, such as imaging techniques and serum-based tests. However, no single test is currently available that is able to completely replace liver biopsy. This review focuses on approved commercial tools used to diagnose HCV infection and the recommended hepatic fibrosis staging tests.